A vertical transition from carbonates to iron formation in the Griqualand West sequence from Finsch mine - Lamprecht, Dirk Ferdinand (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1997.